ANTI-ALLERGY POTENTIAL OF PETIS EXTRACT ON IMMUNOGLOBULIN E PRODUCTION BY U266 CELLS: (Potensi Anti-alergi Ekstrak Petis terhadap Produksi Imunoglobulin E oleh Sel U266) - Rosalind Vivia Tansy; Agus Budiawan Naro Putra; Takuya Sugahara (jurnal1, 2018)
Petis, one of Indonesia’s traditional condiment, is most often made from shrimp andshrimp waste. This condiment becomes popular as a savory flavor additive which is mainly produced in East Java, Indonesia. Despite the unique taste and good nutritionalcontent, any particular study regarding its health benefit in Indonesia has not thoroughly evaluated yet. Therefore, the objective of this research was to explore petis potential towards anti-allergy property in vitro. The potential property was evaluated by determining the concentration of Immunoglobulin E (IgE) by U266 cells treated with petis extract using ELISA. In result, petis extract could significantly suppressed IgE production up to 2-fold atits highest concentration compared to control. Further investigation to extrapolate petis functional bioactive compound was conducted by treating petis extract with heat and enzyme (proteinase K). Result showed that heat-and enzyme-treated petis extract still have the ability to suppress IgE production by U266 cells. Thus,it could be assumed that the functional bioactive compound was a heat-stable non-protein compound. Thesepreliminary findings could conclude that petis extract has a potential anti-allergy propertywhich gives an added value towards petis product in Indonesia.